Border Violence, Democracy, and the Museum. Issue 1 (1st July 2021) - Knell, Simon
Abstract: This article is a re-edited version of the opening prelude to the author's The Museum's Borders: On the Challenge of Knowing and Remembering Well (Routledge, 2021). Based on reportage concerning the Windrush scandal, this article makes the case for the museum to be understood as an autonomous institution critical to knowledge-based democracies. The scandal, exposed in 2018, was the result of the British Government's "hostile environment, " a brutal approach to immigration that ensnared historic migrants to Britain from the Caribbean. Resulting in state violence against Black British citizens, it revealed the degree to which Britain remained mired in institutional racism. Museums, libraries, and other cultural institutions played a critical role in recovering and asserting the history and legitimacy of these people.